Chinmo defines the region-specific oncogenic competence in the Drosophila central nervous system - Phuong-Khanh Nguyen; Francesca Froldi; John P. D. McMullen; Tony D. Southall; Owen J. Marshall; Louise Y. Cheng (Proceedings of the National Academy of Sciences, 2026)
While genetic mutations can promote hyperplastic growth, they do not always result in oncogenic outcomes. We and others have previously identified the transcription factors Nerfin-1 and Lola as inhibitors of dedifferentiation. Here, we investigate how the oncogenic potential of dedifferentiation varies across different neural lineages in the Drosophila central nervous system. We found that Nerfin-1 inactivation causes tumorigenic phenotypes in the central brain and the ventral nerve cord but not the optic lobes (OLs). In contrast, Lola inactivation leads to tumor overgrowth specifically in the OLs. We identify Chinmo, a temporal transcription factor, and its regulation by ecdysone signaling as key determinants of the oncogenic competence in different regions of the brain, influencing the tumorigenic outcome of dedifferentiation. This study provides a fundamental framework to understand how oncogenic competence arises beyond genetic mutations.